Postendodontic Pain after Pulpotomy or Root Canal Treatment in Mature Teeth with Carious Pulp Exposure: A Multicenter Randomized Controlled Trial - Mohammad Jafar Eghbal; Ali Haeri; Arash Shahravan; Ali Kazemi; Fariborz Moazami; Mohammad Ali Mozayeni; Eshaghali Saberi; Mohammad Samiei; Mehdi Vatanpour; Alireza Akbarzade Baghban; Mahta Fazlyab; Ardavan Parhizkar; et al. (Pain Research and Management)
This equivalence, randomized, clinical trial aimed to compare the postoperative pain of root canal therapy (RCT) with pulpotomy with mineral trioxide aggregate (PMTA) or calcium-enriched mixture (PCEM) in permanent mature teeth. In seven academic centers, 550 cariously exposed pulps were included and randomly allocated into PMTA (n = 188), PCEM (n = 194), or RCT (n = 168) arms. Preoperative “Pain Intensity” (PI) on Numerical Rating Scale and postoperative PIs until day 7 were recorded. Patients’ demographic and pre-/intra-/postoperative factors/conditions were recorded/analysed. The arms were homogeneous in terms of demographics. The mean preoperative PIs were similar (P=0.998), the mean sum PIs recorded during 10 postoperative intervals were comparable (P=0.939), and the trend/changes in pain relief were parallel (P=0.821) in all study arms. The incidences of preoperative moderate-severe pain in RCT, PMTA, and PCEM arms were 56.5%, 55.7%, and 56.7%, which after 24 hours considerably decreased to 13.1%, 10.6%, and 12.9%, respectively (P=0.578). The time span of endodontic procedures was statistically different; RCT = 69.73, PMTA = 35.37, and PCEM = 33.62 minutes (P<0.001). Patients with greater preoperative pain, symptomatic apical periodontitis, or presence of PDL widening suffered more pain (P=0.002, 0.035, and 0.023, resp.); however, other pre-/intra-/postoperative factors/conditions were comparable. Pulpotomy with MTA/CEM and RCT demonstrate comparable and effective postoperative pain relief.